2016
DOI: 10.1186/s12957-016-0847-z
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 is related with clinical stage of papillary thyroid carcinoma

Abstract: BackgroundThe context and aim of this article was to investigate whether the expression level of Pin1 was in association with the clinical stage of papillary thyroid carcinomas.MethodsSeventy-two patients who had been treated at the Affiliated Hospital of Qingdao University – Yantai YuHuangDing Hospital during January 2013 to December 2014 were rolled in. The expression levels of Pin1 using immunohistochemistry were tested and were divided into four groups according to the different clinical stages and final s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Pin1 is a key signal-regulating protein in tumors, which is highly expressed in invasive tumors, and is closely related to the development and prognosis of tumors 24 26 . Existing studies have confirmed that Pin1 is involved in the occurrence and development of NPC 14 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Pin1 is a key signal-regulating protein in tumors, which is highly expressed in invasive tumors, and is closely related to the development and prognosis of tumors 24 26 . Existing studies have confirmed that Pin1 is involved in the occurrence and development of NPC 14 , 24 .…”
Section: Discussionmentioning
confidence: 99%